The diversity of Sargassum spp. from the south coast of Yogyakarta, Indonesia, based on morphological characters and DNA Barcoding ITS2 nrDNA - MEGA TRI SARASWATI; RATIH IDA ADHARINI; EKO HARDIANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Saraswati M, Adharini RI, Hardianto E. 2024. The diversity of Sargassum spp. from the south coast of Yogyakarta, Indonesia, based on morphological characters and DNA Barcoding ITS2 nrDNA. Biodiversitas 25: 2733-2739. The genus Sargassum grows abundantly on the south coast of Yogyakarta, but diversity of species in the genus has not been reported. This research aimed to determine the diversity of the genus Sargassum based on morphological characters and molecular analysis. Several samples were collected from two beaches on the south coast of Yogyakarta, namely Trenggole and Wediombo Beach. After observing the morphological characters, five individuals that have morphological differences were found and continued for molecular identification. The morphological analysis showed a characteristic of greenish-brown color, clear phylloids with serrated edges, and rounded vesicles. The results of DNA barcoding identification of Sargassum in Trenggole Beach were highly similar at 99.67% to Sargassum aquifolium (Turner) C.Agardh (MG731834.1), 99.68% to Sargassum yinggehaiense Tseng and Lu (KP101256.1), and 98.99% to Sargassum polycystum C.Agardh (MG731836.1). Whereas at Wediombo Beach were highly similar at 99.68% to S. yinggehaiense (KP101256.1) and 99.67% to S. aquifolium (MG731834.1). Based on phylogenetic analysis, the species were separated impacting the biodiversity of the genus Sargassum in the south coast of Yogyakarta, Indonesia. Environmental factors might influence the morphotype, biodiversity, genetic diversity, and distribution of Sargassum spp. The results described herein provide a foundation for developing better conservation strategies for the target species in the future.